Study on the collaborative protective mechanism of Scutellariae Radix and Paeoniae Radix Alba against diabetic cardiomyopathy through the gut-heart axis - Fang, Cheng; Xu, Xiaomin; Lu, Fang; Liu, Shumin (Frontiers in Microbiology, 2025)
The modification of gut microbiota has been linked to diabetic cardiomyopathy, yet the precise mechanisms through which gut microbes impact cardiac injury remain unclear. Our study concentrated on the gut microorganisms, the intestinal mucosal barrier, and the metabolic pathways involving glucose and lipids in mice afflicted with diabetic cardiomyopathy, while also investigating the cardioprotective properties of Scutellariae Radix and Paeoniae Radix Alba. Using a db (Leptin receptor gene-deficient mouse) mouse model of diabetic cardiomyopathy, we observed that these mice exhibited a decline in the diversity of intestinal microbes, alterations in the abundance of diabetes-related microorganisms, a decrease in Firmicutes, an increase in Helicobacter, and an overall rise in intestinal microbial populations. We pinpointed the inflammatory response and the compromised permeability of the intestinal lining as key contributors to the decline of the intestinal mucosal barrier, subsequently leading to cardiac injury. Administering Scutellariae Radix and Paeoniae Radix Alba was shown to restore the equilibrium of the intestinal microbiota, modify metabolic pathways involving glycerophospholipids, arachidonic acid, and additional metabolites within the myocardial tissue through bile acid, taurine, and associated metabolic processes, resulting in lessened cardiac dysfunction, hypertrophy, and fibrosis in the diabetic cardiomyopathy mice. In conclusion, our findings indicate that the intestinal microbiota, intestinal mucosal barrier, and glycolipid metabolism are disrupted in mice with diabetic cardiomyopathy; however, Scutellariae Radix and Paeoniae Radix Alba may effectively reverse these alterations. These results offer valuable insights for creating therapeutic strategies aimed at mitigating cardiac damage linked to diabetes by focusing on the gut microbiota and glucose and lipid metabolism.